Teleaudiology and calling for engineering collaboration: A state of art review - Rashid M.F.N.; Isa M.R.; Awang M.A.; Kar Q.T.; Zakaria M.N. (American Institute of Physics Inc., 2024)
Teleaudiology is a part of the telehealth approach, and technology was used to deliver audiology and information services to clients using ICT applications such as telephone, email, and video conferencing. Despite this service's benefits, the collaboration between audiologists and engineers is essential to maximize the teleaudiology application. Therefore, this state-of-the-art review aims to summarize and discuss the current evidence on the teleaudiology approach, focusing on technology and applications. A search strategy of database Scopus, Web of Science (WoS), and PubMed were conducted in December 2020, and 13 relevant articles were identified. The inclusion criteria were teleaudiology studies conducted in all countries or regions, articles written in English, and were defined in terms of participants, intervention(s), comparators or controls, outcomes, and study design (PICOS). The review describes three main components: screen sharing or remote access, audio-visual communication, and other technology related to engineering development. In this review, specific research projects can be carried out through audiologists and engineers collaboration such as High-Tech Teleaudiology Van (HTTv) and developing several simulators for the teleaudiology training purposed. In conclusion, having a system such as teleaudiology, comparable audiological services can be conveniently offered to patients, in conjunction with other benefits and collaboration. 2023 Author(s).